Multi Control: um sistema para experimentação de poéticas da realidade virtual em ambiente imersivo e interativo - Oliveira, Edvanilson Santos de (2019)
This research presents the design, development and validation of Multi Control, a low cost system, built based on the Arduino prototyping platform and the use of power interfaces, designed with the objective of facilitating the process of creating and experimenting with immersive and interactive based on the use of microcontrollers. In this context, the central question of our research is: to what extent, and how, does Multi Control contribute to the creation and experimentation of multisensory installations? In this sense, what kind of inputs and outputs are required to enable an immersive / interactive environment? To answer the proposed question, an immersive / interactive installation using Virtual Reality (VR) and Bluetooth communication module, which we call Sentiendum, was designed. In Sentiendum, we seek to analyze the possibilities and limitations of the developed system, as well as to evaluate which poetic aspects of VR may emerge from the immersive / interactive environment. It was elaborated as theoretical contribution, the articulation of historical and conceptual aspects inherent to the Arduino prototyping platform, Interactive Art and Virtual Reality, Body and Perception. Throughout the research, we adopted participatory design as a methodological approach, through a workshop on the use of Arduino in Arts, concurrently conducted the Contemporary Art and Technology Workshop course of the Bachelor of Visual Arts at the Federal University of Mato Grosso do Sul - UFMS. The research was divided into four steps: (1) immersion / understanding of the problem, (2) prototyping and solution design, (3) creation and experimentation of an immersive / interactive installation, (4) virtual environment design. The work resulted in distinct contributions, both regarding the acquisition of artists' knowledge, the relevance of the interface and the application itself in an artistic process, as in this case the creation of Sentiendum